1991
DOI: 10.1021/bi00103a007
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequence of the blue copper protein rusticyanin from Thiobacillus ferrooxidans

Abstract: Rusticyanin is a small blue copper protein isolated from Thiobacillus ferrooxidans. The amino acid sequence of the rusticyanin has been determined by the structural characterization of tryptic and endoproteinase Asp-N peptides with use of amino terminal microsequencing, fast atom bombardment mass spectrometry, and electrospray triple-quadrupole mass spectrometry techniques. Amino acid analysis, carboxy-terminal sequence analysis, and circular dichroism spectroscopy were also performed on the protein. Amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 30 publications
1
48
0
Order By: Relevance
“…1). For rusticyanin one of the coordinating histidines could not be located in the primary sequence [22,23]. It has been suggested that its position might be taken up by an aspartate [23].…”
Section: Type 1 Copper Sitesmentioning
confidence: 99%
“…1). For rusticyanin one of the coordinating histidines could not be located in the primary sequence [22,23]. It has been suggested that its position might be taken up by an aspartate [23].…”
Section: Type 1 Copper Sitesmentioning
confidence: 99%
“…1) from this known sequence of strain ATCC 23270. 21) These primers were used to amplify and clone rus from several strains of the bacterium. This strategy was successful for cloning rus of several strains.…”
Section: Resultsmentioning
confidence: 99%
“…The rusticyanin open reading frame was cloned by PCR using genomic DNA with the primers. The primers for PCR were based on the previously identiˆed rus gene, 21,22) or on the new gene identiˆed here. The primers are summarized in Table 1 and Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations